Korkean pelaajapysyvyyden saavuttaminen videopeleissä - Kariluoto, Antti Juho Aleksi (2024)
The modern video game business model is quickly transitioning into one based on retaining the game’s customers for an extended period of time, offering the player in-game purchases or monthly subscriptions. The objective of this thesis was to find out how game developers can attain high player retention in their games and figure out which strategies to implement in order to stop players from leaving their game. It was discovered that a game should contain different activities or roles for different types of players, allowing each player to derive satisfaction from their desired activities. Additionally, high reteniton was ifound to be based on identifying players who were about to permamently stop playing the game and respectively attempting to prevent them from leaving. According to the findings, a leaving player can most efficiently be identified using machine learning algorithms, after which the player can potentially be persuaded to stay active using in-game gifts or sending them personalized messages.